High-frequency high-speed phenolic resin-based copper-clad plate and preparation method thereof
By using lamination molding technology of high-frequency high-speed phenolic resin-based materials and composite resins in the preparation of copper clad plates, the problem of signal attenuation and distortion of traditional copper clad plates under high-frequency signals is solved, and antibacterial performance and thermal stability are improved, achieving more stable signal transmission and longer product life.
Patent Information
- Application Number
- CN202411764488.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-04
- Publication Date
- 2025-02-28
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Traditional copper clad plates have signal attenuation and distortion problems under high-frequency signals, and electronic waste has negative impacts on the environment.
Using the preparation method of high-frequency high-speed phenolic resin-based copper clad plate, azalkon aromatic hydrocarbons were synthesized through Mannich reaction and Williamson reaction, and mixed with phosphonium bromide product and dibenzoyl peroxide, and then warmed up to obtain a composite resin, combined with phenolic resin, butanone, flame retardant, filler and accelerator, and laminated to obtain the finished product.
It achieves the reduction of dielectric constant, reduces signal loss and improves signal integrity, has good antibacterial performance and thermal stability, extends the life of electronic products and reduces environmental pollution.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of copper clad laminate preparation, in particular to a high-frequency and high-speed phenolic resin-based copper clad laminate and a preparation method thereof. Background Art
[0002] With the development and popularization of electronic products, the demand for products such as mobile phones, tablets, and computers has gradually increased. In order to meet the demand for circuit boards for these products, copper clad laminates, as a type of sheet made of copper on the surface of a substrate, have important value in manufacturing, carrying and connecting electronic components. They can provide good conductivity and mechanical strength, and ensure the connection and stability between electronic components. However, traditional copper clad laminates have problems with signal attenuation and distortion under high-frequency signals. In order to solve this problem, high-frequency and high-speed phenolic resin-based copper clad laminates came into being. This type of copper clad laminate has good high-frequency characteristics, can effectively reduce signal attenuation and distortion, and provide more stable signal transmission performance. Therefore, in modern communication technology, the transmission of high-frequency signals has become a normalized demand. High-frequency and high-speed phenolic resin-based copper clad laminates usually have lower dielectric loss and higher dielectric constant. This design is intended to ensure that copper clad laminates provide lower signal loss and better signal integrity. In addition, electronic waste has a serious negative impact on the environment. Antibacterial copper clad laminates can provide an additional layer of protection to inhibit bacterial growth and reduce the risk of early equipment failure due to bacterial erosion. Therefore, preparing antibacterial copper clad laminates can extend the life of electronic products and reduce the negative impact on the environment.
[0003] In order to overcome the defects of the prior art, the present invention provides a high-frequency and high-speed phenolic resin-based copper clad laminate and a preparation method thereof. Summary of the invention
[0004] The object of the present invention is to provide a high-frequency and high-speed phenolic resin-based copper-clad laminate and a preparation method thereof, so as to solve the problems in the prior art.
[0005] In order to solve the above technical problems, the present invention provides the following technical solutions:
[0006] A method for preparing a high-frequency and high-speed phenolic resin-based copper-clad laminate comprises the following steps:
[0007] Step 1: 4,4-dihydroxydiphenylmethane, polyformaldehyde, 2-bromo-6-fluoroaniline and toluene are mixed, and refluxed at 90-100° C. for 4-6 hours. After the reaction is completed, the mixture is cooled, rotary evaporated and recrystallized to obtain a benzoxazine monomer; the benzoxazine monomer is heated in stages to obtain an intermediate product, and the intermediate product is dissolved in n-butanol, and potassium hydroxide and 4-chloromethylstyrene are added under a nitrogen environment, and the mixture is reacted at 60-70° C. for 4-5 hours. After the reaction is completed, the mixture is cooled, precipitated and vacuum dried to prepare azacalixarene;
[0008] Step 2: 9-bromo-1-nonanol, triethylamine and dichloromethane are mixed, stirred fully, and then 2-chloro-1,3-butadiene is added dropwise at 0-5°C, reacted at 0-5°C for 2-3h, and then continued to react at 25-30°C for 25-30h. After the reaction, the mixture is subjected to rotary evaporation, purification and drying to obtain a bromide product; the bromide product, triphenylphosphine, hydroquinone and acetonitrile are mixed, stirred fully, and then reacted at 80-90°C for 60-65h. After the reaction, the mixture is subjected to rotary evaporation, purification and drying to obtain a phosphonium bromide product; azacalixarene, phosphonium bromide product and dibenzoyl peroxide are mixed and placed in a mold, and heated in stages to obtain a composite resin;
[0009] Step 3: Mix phenolic resin, composite resin and butanone, stir until dissolved, then add flame retardant, filler and accelerator, stir thoroughly to obtain resin glue; immerse glass fiber cloth in the resin glue, and obtain a semi-cured sheet through high temperature curing; overlap copper foil on both sides of the semi-cured sheet, and prepare a finished product after lamination.
[0010] More optimally, in step 1, the reaction molar ratio of 4,4-dihydroxydiphenylmethane, polyformaldehyde, 2-bromo-6-fluoroaniline and 4-chloromethylstyrene is 1:3:2:5-7.
[0011] More optimally, in step one, the temperature is increased in stages: heating at 100-120°C for 4-5h, heating at 150-180°C for 4-5h.
[0012] More optimally, in step 2, the contents of the components of the phosphonium bromide product are: by mass, 25-30 parts of 9-bromo-1-nonanol, 20-25 parts of triethylamine, 150-160 parts of dichloromethane, 15-20 parts of 2-chloro-1,3-butadiene, 65-70 parts of triphenylphosphine, 0.5-0.6 parts of hydroquinone, and 150-200 parts of acetonitrile.
[0013] More optimally, in step 2, when preparing the composite resin, the mass ratio of azacalixarene, phosphonium bromide product and dibenzoyl peroxide is 5:1-1.5:0.1.
[0014] More optimally, in step 2, the temperature is increased in stages: heating at 150-170°C for 1-2h, heating at 180-200°C for 1-2h.
[0015] More optimally, in step three, the contents of the components of the resin glue are: by mass fraction, 30-40% phenolic resin, 20-25% composite resin, 10-15% butanone, 10-15% flame retardant, 1-2% accelerator, and the remainder is filler.
[0016] More optimally, the flame retardant is ammonium phosphate, the accelerator is di-tert-butyl peroxyisopropylbenzene, and the filler is silicon micropowder.
[0017] More optimally, in step three, high temperature curing is performed at 150-200°C for 5-10 minutes.
[0018] More optimally, in step three, the lamination process parameters are: temperature of 180-200°C, pressure of 2-4MPa, and time of 1-2h.
[0019] Beneficial effects of the present invention:
[0020] The present invention prepares azacalixarene by adding 4,4-dihydroxydiphenylmethane, paraformaldehyde, 2-bromo-6-fluoroaniline, potassium hydroxide, 4-chloromethylstyrene and solvent. Then, 9-bromo-1-nonanol, triethylamine, dichloromethane, 2-chloro-1.3-butadiene, triphenylphosphine, hydroquinone and acetonitrile are used as raw materials to prepare a phosphonium bromide product. Azacalixarene, a phosphonium bromide product and dibenzoyl peroxide are mixed and placed in a mold, and a composite resin is obtained by stage heating. A resin glue is prepared by adding phenolic resin, a composite resin, butanone, a flame retardant, a filler and an accelerator. Finally, a glass fiber cloth is impregnated in the resin glue, and a semi-cured sheet is obtained by high-temperature curing; copper foil is overlapped on both sides of the semi-cured sheet, and a finished product is obtained by lamination.
[0021] The feature of the present invention is that in step one, the present invention prepares azacalixarene by adding 4,4-dihydroxydiphenylmethane, paraformaldehyde, 2-bromo-6-fluoroaniline, potassium hydroxide, 4-chloromethylstyrene and solvent. The reaction principle is: 4,4-dihydroxydiphenylmethane, paraformaldehyde and 2-bromo-6-fluoroaniline synthesize benzoxazine monomers through Mannich reaction, and then the benzoxazine monomers are heated at high temperature to obtain a reaction intermediate, and the intermediate and 4-chloromethylstyrene are subjected to Williamson reaction to prepare azacalixarene. The azacalixarene prepared by the present invention contains nanocavities with large free volume and a large number of fluorine atoms. The dielectric constant can be effectively reduced by increasing the molecular free volume. The molecular polarity can be effectively reduced and the molecular free volume can be increased by introducing fluorine atoms, thereby reducing the dielectric constant and meeting the high-frequency and high-speed requirements of copper-clad laminates.
[0022] The present invention is characterized in that, in step 2, 9-bromo-1-nonanol, triethylamine, dichloromethane, 2-chloro-1,3-butadiene, triphenylphosphine, hydroquinone and acetonitrile are used as raw materials to prepare a phosphonium bromide product. In this step, 9-bromo-1-nonanol and 2-chloro-1,3-butadiene can react to generate a bromide product; and then the bromide product is reacted with triphenylphosphine to generate a phosphonium bromide product. The phosphonium bromide product contains a quaternary phosphonium salt group and a halogen, so it has good antibacterial properties and thermal stability, can effectively inhibit bacterial growth and improve the high temperature resistance of the copper clad laminate. In addition, in step 1, a carbon-carbon double bond structure is introduced into the azacalixarene by adding 4-chloromethylstyrene, and in step 2, a carbon-carbon double bond structure is introduced into the phosphonium bromide product by adding 2-chloro-1.3-butadiene, and finally the azacalixarene, the phosphonium bromide product and the initiator dibenzoyl peroxide are mixed, and a free radical polymerization reaction is carried out under high temperature conditions to prepare a composite resin. The composite resin can have good dielectric properties, antibacterial properties and thermal stability, and has broad application prospects in the field of copper clad laminate preparation technology. DETAILED DESCRIPTION
[0023] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0024] Source of raw materials:
[0025] Paraformaldehyde, provided by Shanghai McLean Biochemical Technology Co., Ltd., with a purity of 95%; phenolic resin, provided by Hubei Xinghengye Technology Co., Ltd., with an industrial grade; silicon micropowder, provided by Lingshou County Longchuang Mineral Products Co., Ltd., with a particle size of 1250 mesh; glass fiber cloth, provided by Taiwan Taijia Chengdu Glass Fiber Co., Ltd., with an industrial grade; copper foil, provided by Kunshan Luzhifa Electronic Technology Co., Ltd., with a thickness of 0.07mm. In terms of mass, one portion is 1g.
[0026] Example 1: Step 1: 1 mol of 4,4-dihydroxydiphenylmethane, 3 mol of polyformaldehyde, 2 mol of 2-bromo-6-fluoroaniline and 300 g of toluene were mixed, and refluxed at 100° C. for 6 h. After the reaction was completed, the mixture was cooled, rotary evaporated and recrystallized to obtain a benzoxazine monomer; the benzoxazine monomer was heated at 120° C. for 5 h and 180° C. for 5 h in sequence to obtain an intermediate product, and the intermediate product was dissolved in 200 g of n-butanol, and 150 g of potassium hydroxide and 5 mol of 4-chloromethylstyrene were added under a nitrogen environment, and the mixture was reacted at 70° C. for 5 h. After the reaction was completed, the mixture was cooled, precipitated and vacuum dried to prepare azacalixarene;
[0027] Step 2: 20g 9-bromo-1-nonanol, 20g triethylamine and 150g dichloromethane are mixed, stirred fully, and then 15g 2-chloro-1.3-butadiene is added dropwise at 5°C. After the addition is completed, the mixture is reacted at 5°C for 3h, and then at 30°C for 30h. After the reaction is completed, the mixture is subjected to rotary evaporation, purification and drying to obtain a bromide product; the bromide product, 65g triphenylphosphine, 0.5g hydroquinone and 150g acetonitrile are mixed, stirred fully, and then reacted at 90°C for 65h. After the reaction is completed, the mixture is subjected to rotary evaporation, purification and drying to obtain a phosphonium bromide product; 5g azacalixarene, 1g phosphonium bromide product and 0.1g dibenzoyl peroxide are mixed and placed in a mold, and heated at 170°C for 2h and 200°C for 2h in sequence to obtain a composite resin;
[0028] Step 3: Mix 40% phenolic resin, 25% composite resin and 15% butanone by mass fraction, stir until dissolved, then add 10% ammonium phosphate, 9% silicon powder and 1% di-tert-butyl peroxyisopropylbenzene, and stir thoroughly to obtain resin glue; immerse the glass fiber cloth in the resin glue, and cure it at 200°C for 10 minutes to obtain a semi-cured sheet; overlap copper foil on both sides of the semi-cured sheet, and laminate for 2 hours at a temperature of 200°C and a pressure of 4Mpa to obtain a finished product.
[0029] Example 2: Step 1: 1 mol of 4,4-dihydroxydiphenylmethane, 3 mol of polyformaldehyde, 2 mol of 2-bromo-6-fluoroaniline and 300 g of toluene were mixed, and the mixture was refluxed at 97° C. for 5.5 h. After the reaction was completed, the mixture was cooled, rotary evaporated and recrystallized to obtain a benzoxazine monomer; the benzoxazine monomer was heated at 115° C. for 4.7 h and 170° C. for 4.7 h in sequence to obtain an intermediate product, and the intermediate product was dissolved in 200 g of n-butanol, and 150 g of potassium hydroxide and 5 mol of 4-chloromethylstyrene were added under a nitrogen environment, and the mixture was reacted at 67° C. for 4.7 h. After the reaction was completed, the mixture was cooled, precipitated and vacuum dried to prepare azacalixarene;
[0030] Step 2: 20g 9-bromo-1-nonanol, 20g triethylamine and 150g dichloromethane are mixed, stirred fully, and then 15g 2-chloro-1.3-butadiene is added dropwise at 4°C. After the addition is completed, the mixture is reacted at 4°C for 2.7h, and then at 29°C for 29h. After the reaction is completed, the mixture is subjected to rotary evaporation, purification and drying to obtain a bromide product; the bromide product, 65g triphenylphosphine, 0.5g hydroquinone and 150g acetonitrile are mixed, stirred fully, and then reacted at 87°C for 64h. After the reaction is completed, the mixture is subjected to rotary evaporation, purification and drying to obtain a phosphonium bromide product; 5g azacalixarene, 1g phosphonium bromide product and 0.1g dibenzoyl peroxide are mixed and placed in a mold, and heated at 165°C for 1.7h and 195°C for 1.7h to obtain a composite resin;
[0031] Step 3: Mix 40% phenolic resin, 25% composite resin and 15% butanone by mass, stir until dissolved, then add 10% ammonium phosphate, 9% silicon powder and 1% di-tert-butyl peroxyisopropylbenzene, and stir thoroughly to obtain resin glue; immerse the glass fiber cloth in the resin glue, and cure it at 190°C for 9 minutes to obtain a semi-cured sheet; overlap copper foil on both sides of the semi-cured sheet, and laminate for 1.7 hours at a temperature of 195°C and a pressure of 3.5Mpa to obtain a finished product.
[0032] Example 3: Step 1: 1 mol of 4,4-dihydroxydiphenylmethane, 3 mol of polyformaldehyde, 2 mol of 2-bromo-6-fluoroaniline and 300 g of toluene were mixed, and the mixture was refluxed at 95° C. for 5 h. After the reaction was completed, the mixture was cooled, rotary evaporated and recrystallized to obtain a benzoxazine monomer; the benzoxazine monomer was heated at 110° C. for 4.5 h and 165° C. for 4.5 h in sequence to obtain an intermediate product, and the intermediate product was dissolved in 200 g of n-butanol, and 150 g of potassium hydroxide and 5 mol of 4-chloromethylstyrene were added under a nitrogen environment, and the mixture was reacted at 65° C. for 4.5 h. After the reaction was completed, the mixture was cooled, precipitated and vacuum dried to prepare azacalixarene;
[0033] Step 2: 20g 9-bromo-1-nonanol, 20g triethylamine and 150g dichloromethane are mixed and stirred fully, and then 15g 2-chloro-1.3-butadiene is added dropwise at 2°C, and the mixture is reacted at 2°C for 2.5h, and then at 27°C for 27h. After the reaction, the mixture is subjected to rotary evaporation, purification and drying to obtain a bromide product; the bromide product, 65g triphenylphosphine, 0.5g hydroquinone and 150g acetonitrile are mixed and stirred fully, and then reacted at 85°C for 63h. After the reaction, the mixture is subjected to rotary evaporation, purification and drying to obtain a phosphonium bromide product; 5g azacalixarene, 1g phosphonium bromide product and 0.1g dibenzoyl peroxide are mixed and placed in a mold, and heated at 160°C for 1.5h and 190°C for 1.5h to obtain a composite resin;
[0034] Step 3: Mix 40% phenolic resin, 25% composite resin and 15% butanone by mass fraction, stir until dissolved, then add 10% ammonium phosphate, 9% silicon powder and 1% di-tert-butyl peroxyisopropylbenzene, and stir thoroughly to obtain resin glue; immerse the glass fiber cloth in the resin glue, and cure it at 170°C for 7 minutes to obtain a semi-cured sheet; overlap copper foil on both sides of the semi-cured sheet, and laminate for 1.5 hours at a temperature of 190°C and a pressure of 2.5Mpa to obtain a finished product.
[0035] Example 4: Step 1: 1 mol of 4,4-dihydroxydiphenylmethane, 3 mol of polyformaldehyde, 2 mol of 2-bromo-6-fluoroaniline and 300 g of toluene were mixed, and the mixture was refluxed at 93° C. for 4.5 h. After the reaction was completed, the mixture was cooled, rotary evaporated and recrystallized to obtain a benzoxazine monomer; the benzoxazine monomer was heated at 105° C. for 4.3 h and 160° C. for 4.3 h in sequence to obtain an intermediate product, and the intermediate product was dissolved in 200 g of n-butanol, and 150 g of potassium hydroxide and 5 mol of 4-chloromethylstyrene were added under a nitrogen environment, and the mixture was reacted at 63° C. for 4.3 h. After the reaction was completed, the mixture was cooled, precipitated and vacuum dried to prepare azacalixarene;
[0036] Step 2: 20g 9-bromo-1-nonanol, 20g triethylamine and 150g dichloromethane are mixed, stirred fully, and then 15g 2-chloro-1.3-butadiene is added dropwise at 1°C, reacted at 1°C for 2.3h, and then continued to react at 26°C for 26h. After the reaction, the mixture is subjected to rotary evaporation, purification and drying to obtain a bromide product; the bromide product, 65g triphenylphosphine, 0.5g hydroquinone and 150g acetonitrile are mixed, stirred fully, and then reacted at 83°C for 61h. After the reaction, the mixture is subjected to rotary evaporation, purification and drying to obtain a phosphonium bromide product; 5g azacalixarene, 1g phosphonium bromide product and 0.1g dibenzoyl peroxide are mixed and placed in a mold, and heated at 155°C for 1.3h and 185°C for 1.3h to obtain a composite resin;
[0037] Step 3: Mix 40% phenolic resin, 25% composite resin and 15% butanone by mass, stir until dissolved, then add 10% ammonium phosphate, 9% silicon powder and 1% di-tert-butyl peroxyisopropylbenzene, and stir thoroughly to obtain resin glue; immerse the glass fiber cloth in the resin glue, and cure it at 160°C for 6 minutes to obtain a semi-cured sheet; overlap copper foil on both sides of the semi-cured sheet, and laminate for 1.3 hours at a temperature of 185°C and a pressure of 2.3Mpa to obtain a finished product.
[0038] Example 5: Step 1: 1 mol of 4,4-dihydroxydiphenylmethane, 3 mol of polyformaldehyde, 2 mol of 2-bromo-6-fluoroaniline and 300 g of toluene were mixed, and the mixture was refluxed at 90° C. for 4 h. After the reaction was completed, the mixture was cooled, rotary evaporated and recrystallized to obtain a benzoxazine monomer; the benzoxazine monomer was heated at 100° C. for 4 h and 150° C. for 4 h in sequence to obtain an intermediate product, and the intermediate product was dissolved in 200 g of n-butanol, and 150 g of potassium hydroxide and 5 mol of 4-chloromethylstyrene were added under a nitrogen environment, and the mixture was reacted at 60° C. for 4 h. After the reaction was completed, the mixture was cooled, precipitated and vacuum dried to prepare azacalixarene;
[0039] Step 2: 20g 9-bromo-1-nonanol, 20g triethylamine and 150g dichloromethane are mixed and stirred fully, and then 15g 2-chloro-1.3-butadiene is added dropwise at 0°C, and the mixture is reacted at 0°C for 2h and then at 25°C for 25h. After the reaction, the mixture is subjected to rotary evaporation, purification and drying to obtain a bromide product; the bromide product, 65g triphenylphosphine, 0.5g hydroquinone and 150g acetonitrile are mixed and stirred fully, and then the mixture is reacted at 80°C for 60h. After the reaction, the mixture is subjected to rotary evaporation, purification and drying to obtain a phosphonium bromide product; 5g azacalixarene, 1g phosphonium bromide product and 0.1g dibenzoyl peroxide are mixed and placed in a mold, and heated at 150°C for 1h and 180°C for 1h in sequence to obtain a composite resin;
[0040] Step 3: Mix 40% phenolic resin, 25% composite resin and 15% butanone by mass fraction, stir until dissolved, then add 10% ammonium phosphate, 9% silicon powder and 1% di-tert-butyl peroxyisopropylbenzene, and stir thoroughly to obtain resin glue; immerse the glass fiber cloth in the resin glue, and cure it at 150°C for 5 minutes to obtain a semi-cured sheet; overlap copper foil on both sides of the semi-cured sheet, and laminate for 1 hour at a temperature of 180°C and a pressure of 2Mpa to obtain a finished product.
[0041] Comparative Example 1: The preparation step of azacalixarene is removed, and the rest is the same as Example 1, and the specific steps are as follows: Step 1: 20g of 9-bromo-1-nonanol, 20g of triethylamine and 150g of dichloromethane are mixed, fully stirred, and then 15g of 2-chloro-1.3-butadiene is added dropwise at 5°C, reacted at 5°C for 3h, and then continued to react at 30°C for 30h. After the reaction, the brominated product is prepared by rotary evaporation, purification and drying; the brominated product, 65g of triphenylphosphine, 0.5g of hydroquinone and 150g of acetonitrile are mixed, fully stirred, and then reacted at 90°C for 65h. After the reaction, the product is rotary evaporated, purified and dried to prepare a phosphonium bromide product; 1g of the phosphonium bromide product and 0.1g of dibenzoyl peroxide are mixed and placed in a mold, and heated at 170°C for 2h and 200°C for 2h in sequence to prepare an antibacterial material;
[0042] Step 2: Mix 40% phenolic resin, 25% antibacterial material and 15% butanone by mass, stir until dissolved, then add 10% ammonium phosphate, 9% silicon powder and 1% di-tert-butyl peroxyisopropylbenzene, and stir thoroughly to obtain resin glue; immerse the glass fiber cloth in the resin glue, and cure it at 200°C for 10 minutes to obtain a semi-cured sheet; overlap copper foil on both sides of the semi-cured sheet, and laminate for 2 hours at a temperature of 200°C and a pressure of 4Mpa to obtain a finished product.
[0043] Comparative Example 2: The preparation step of the phosphonium bromide product is removed, and the rest is the same as Example 1, and the specific steps are as follows: Step 1: 1 mol of 4,4-dihydroxydiphenylmethane, 3 mol of polyformaldehyde, 2 mol of 2-bromo-6-fluoroaniline and 300 g of toluene are mixed, and refluxed at 100° C. for 6 h. After the reaction is completed, the mixture is cooled, rotary evaporated and recrystallized to obtain a benzoxazine monomer; the benzoxazine monomer is heated at 120° C. for 5 h and 180° C. for 5 h in sequence to obtain an intermediate product, and the intermediate product is dissolved in 200 g of n-butanol, and 10 g of potassium hydroxide and 5 mol of 4-chloromethylstyrene are added under a nitrogen environment, and the mixture is reacted at 70° C. for 5 h. After the reaction is completed, the mixture is cooled, precipitated and vacuum dried to obtain azacalixarene;
[0044] Step 2: 5 g of azacalixarene and 0.1 g of dibenzoyl peroxide were mixed and placed in a mold, and heated at 170° C. for 2 h and 200° C. for 2 h in sequence to prepare a composite resin;
[0045] Step 3: Mix 40% phenolic resin, 25% composite resin and 15% butanone by mass fraction, stir until dissolved, then add 10% ammonium phosphate, 9% silicon powder and 1% di-tert-butyl peroxyisopropylbenzene, and stir thoroughly to obtain resin glue; immerse the glass fiber cloth in the resin glue, and cure it at 200°C for 10 minutes to obtain a semi-cured sheet; overlap copper foil on both sides of the semi-cured sheet, and laminate for 2 hours at a temperature of 200°C and a pressure of 4Mpa to obtain a finished product.
[0046] Detection test:
[0047] Dielectric property test: A German Technology 4991A (room temperature) dielectric tester was used to cut the prepreg prepared by the present invention into samples with a size of 10×10×1 mm, and the dielectric constant and dielectric loss of the samples were tested at a frequency of 1 GHz.
[0048] Antibacterial test: First, Staphylococcus aureus bacterial solution was prepared, and the semi-cured sheet prepared by the present invention was cut into a sample with a size of 10×10×1mm. The sample was placed in the bacterial solution and stirred for 10 hours. The concentration of the bacterial solution before and after stirring was measured, and then the sterilization rate was calculated according to the formula. The results are shown in the following table:
[0049] <![CDATA[Dielectric constant D k / (F / m)]]> Dielectric loss Df / (%) Sterilization rate / % Example 1 2.31 3.15 92 Example 2 2.32 3.16 91 Example 3 2.33 3.17 90 Example 4 2.34 3.18 89 Example 5 2.35 3.19 88 Comparative Example 1 2.59 4.86 85 Comparative Example 2 2.33 3.16 75
[0050] Conclusion: The dosage of Examples 1 to 5 remains unchanged, and only some reaction parameters are modified. It can be seen from the experimental data that there is no obvious fluctuation in the various properties of the sample. Comparative Example 1: The preparation step of azacalixarene is removed, and the rest is the same as Example 1. It can be seen from the experimental data that compared with Example 1, the dielectric constant increases to 2.59F / m, the dielectric loss increases to 4.86%, and the sterilization rate decreases to 85%. The reasons are analyzed as follows: azacalixarene can reduce the dielectric constant by increasing the molecular free volume and introducing fluorine atoms. Therefore, after the preparation step of azacalixarene is removed, the dielectric constant and dielectric loss will increase; in addition, since azacalixarene also contains benzene rings and halogen atoms, the antibacterial performance will decrease after the preparation step of azacalixarene is removed.
[0051] Comparative Example 2: The preparation step of the phosphonium bromide product is removed, and the rest is the same as Example 1. It can be seen from the experimental data that the bactericidal rate is reduced to 75% compared with Example 1. The reason for this is that the quaternary phosphonium salt group and halogen in the phosphonium bromide product have good antibacterial properties and can inhibit bacterial growth. Therefore, after the preparation step of the phosphonium bromide product is removed, the bactericidal rate is reduced.
[0052] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variations thereof are intended to cover non-exclusive inclusion, so that a process method article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process method article or device.
[0053] Finally, it should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for preparing a high-frequency and high-speed phenolic resin-based copper-clad laminate, characterized in that: The following steps are involved: Step 1: 4,4-dihydroxydiphenylmethane, polyformaldehyde, 2-bromo-6-fluoroaniline and toluene are mixed, and refluxed at 90-100° C. for 4-6 hours. After the reaction is completed, the mixture is cooled, rotary evaporated and recrystallized to obtain a benzoxazine monomer; the benzoxazine monomer is heated in stages to obtain an intermediate product, and the intermediate product is dissolved in n-butanol, and potassium hydroxide and 4-chloromethylstyrene are added under a nitrogen environment, and the mixture is reacted at 60-70° C. for 4-5 hours. After the reaction is completed, the mixture is cooled, precipitated and vacuum dried to prepare azacalixarene; Step 2: 9-bromo-1-nonanol, triethylamine and dichloromethane are mixed, stirred fully, and then 2-chloro-1,3-butadiene is added dropwise at 0-5°C, reacted at 0-5°C for 2-3h, and then continued to react at 25-30°C for 25-30h. After the reaction, the mixture is subjected to rotary evaporation, purification and drying to obtain a bromide product; the bromide product, triphenylphosphine, hydroquinone and acetonitrile are mixed, stirred fully, and then reacted at 80-90°C for 60-65h. After the reaction, the mixture is subjected to rotary evaporation, purification and drying to obtain a phosphonium bromide product; azacalixarene, phosphonium bromide product and dibenzoyl peroxide are mixed and placed in a mold, and heated in stages to obtain a composite resin; Step 3: Mix phenolic resin, composite resin and butanone, stir until dissolved, then add flame retardant, filler and accelerator, stir thoroughly to obtain resin glue; immerse glass fiber cloth in the resin glue, and obtain a semi-cured sheet through high temperature curing; overlap copper foil on both sides of the semi-cured sheet, and prepare a finished product after lamination.
2. The method for preparing a high-frequency and high-speed phenolic resin-based copper-clad laminate according to claim 1, characterized in that: In step 1, the reaction molar ratio of 4,4-dihydroxydiphenylmethane, polyformaldehyde, 2-bromo-6-fluoroaniline and 4-chloromethylstyrene is 1:3:2:5-7.
3. The method for preparing a high-frequency and high-speed phenolic resin-based copper-clad laminate according to claim 1, characterized in that: In step 1, the temperature is increased in stages: 100-120°C for 4-5h, and 150-180°C for 4-5h.
4. The method for preparing a high-frequency and high-speed phenolic resin-based copper-clad laminate according to claim 1, characterized in that: In step 2, the contents of the components of the phosphonium bromide product are as follows: by mass: 25-30 parts of 9-bromo-1-nonanol, 20-25 parts of triethylamine, 150-160 parts of dichloromethane, 15-20 parts of 2-chloro-1,3-butadiene, 65-70 parts of triphenylphosphine, 0.5-0.6 parts of hydroquinone, and 150-200 parts of acetonitrile.
5. The method for preparing a high-frequency and high-speed phenolic resin-based copper-clad laminate according to claim 1, characterized in that: In step 2, when preparing the composite resin, the mass ratio of azacalixarene, phosphonium bromide product and dibenzoyl peroxide is 5:1-1.5:0.
1.
6. The method for preparing a high-frequency and high-speed phenolic resin-based copper-clad laminate according to claim 1, characterized in that: In step 2, the temperature is increased in stages: 150-170°C for 1-2h, and 180-200°C for 1-2h.
7. The method for preparing a high-frequency and high-speed phenolic resin-based copper-clad laminate according to claim 1, characterized in that: In step three, the contents of the components of the resin glue are as follows: by mass fraction, 30-40% phenolic resin, 20-25% composite resin, 10-15% butanone, 10-15% flame retardant, 1-2% accelerator, and the remainder is filler.
8. The method for preparing a high-frequency and high-speed phenolic resin-based copper-clad laminate according to claim 7, characterized in that: The flame retardant is ammonium phosphate, the accelerator is di-tert-butyl peroxyisopropylbenzene, and the filler is silicon micropowder.
9. The method for preparing a high-frequency and high-speed phenolic resin-based copper-clad laminate according to claim 1, characterized in that: In step three, high temperature curing is performed at 150-200°C for 5-10 minutes.
10. The method for preparing a high-frequency and high-speed phenolic resin-based copper-clad laminate according to claim 1, characterized in that: In step three, the lamination process parameters are: temperature of 180-200°C, pressure of 2-4MPa, and time of 1-2h.
Citation Information
Patent Citations
Phenolic resin-based copper-clad plate and preparation method thereof
CN116080210A